CPU LOAD BASED THREAT PREVENTION FRAMEWORK FOR COVERT CHANNEL ATTACKS - Kunchala Little Flower, Dr.Neeraj Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Numerous virtual machines on a solitary virtual machine mon-itor are segregated from one another. A malignant client on one virtual machine ordinarily can't hand-off restricted information to other virtual machines without utilizing unequivocal correspondence media like shared les or an organization. In any case, this detachment is undermined by correspondence in which CPU load is utilized as a secretive channel. Sadly, this danger has not been completely perceived or assessed. In this review, we quanti-tatively assess the danger of CPU-based secret channels between virtual machines on the Xen hypervisor. We have created CCCV, a framework that makes a clandestine channel and conveys information subtly utilizing CPU loads. CCCV comprises of two client processes, a sender and a beneficiary. The sender runs on one virtual machine, and the beneficiary sudden spikes in demand for one more virtual machine on the equivalent hypervisor. We measured the transfer speed and correspondence precision of the incognito channel. CCCV imparted 64-bit information with a 100% achievement rate in an optimal climate, and with a success pace of more than 90% in a climate where Web servers are handling demands on other virtual machines.